Farmers' voices on the Spoken Web - Nanavati, Amit A.; Agarwal, Sheetal K.; Kumar, Arun; Rajput, Nitendra (Technical Centre for Agricultural and Rural Cooperation, 2009)
A network of voice recordings, accessible from any telephone, provides information to farmers in India. Villagers can add their own VoiceSites to promote their business.